Visible Spectrophotometric Determination of Lomefloxacin in Bulk and Pharmaceutical Dosage Formulations - Srinivas, L.D.; Prasad Rao, K.V.S.; Sastry, B.S. (Asian Journal of Chemistry, 2016)
Two simple and sensitive visible spectrophotometric methods are developed for the estimation of lomefloxacin in its dosage forms. In method A, lomefloxacin reacts with sodium nitroprusside and hydroxylamine hydrochloride in alkaline medium to produce a yellow-coloured chromogen having lmax at 440 nm. Beer's law is obeyed in the concentration range of 15–75 μg. In the method B, lomefloxacin reacts with chloranil and acetaldehyde to give a dark bluish coloured chromogen having lmax at 665 nm. Linearity is 3–15 g. Commercial dosage forms of the drugs have been evaluated by the proposed methods and found satisfactory.